Conditional operations on fuzzy numbers - Nykyforchyn, Kh.O. (Carpathian Mathematical Publications, 2013)
An estimate of a joint possibility distribution of two fuzzy numbers, based on fuzzy relations with a third fuzzy variable, is suggested. This leads to the operations of conditional addition and conditional multiplication, of interactive fuzzy numbers for which joint possibility distributions with a fuzzy variable are known.